2012
DOI: 10.1148/radiol.11111026
|View full text |Cite
|
Sign up to set email alerts
|

Mammographic Interpretive Volume and Diagnostic Mammogram Interpretation Performance in Community Practice

Abstract: Purpose:To investigate the association between radiologist interpretive volume and diagnostic mammography performance in community-based settings. Materials and Methods:This study received institutional review board approval and was HIPAA compliant. A total of 117 136 diagnostic mammograms that were interpreted by 107 radiologists between 2002 and 2006 in the Breast Cancer Surveillance Consortium were included. Logistic regression analysis was used to estimate the adjusted effect on sensitivity and the rates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 22 publications
3
31
1
Order By: Relevance
“…Contrary to the hypothesis suggested by the Institute of Medicine report that a higher interpretive volume would improve mammography performance, a study of a sample of U.S. radiologists found that volume did not explain much of the observed interradiologist variability in screening or diagnostic performance (4,5). The FPRs of radiologists with higher annual volumes were clinically and significantly lower than those of their lower-volume colleagues; however, the sensitivities were similar (4,5).…”
Section: Subjectsmentioning
confidence: 70%
See 3 more Smart Citations
“…Contrary to the hypothesis suggested by the Institute of Medicine report that a higher interpretive volume would improve mammography performance, a study of a sample of U.S. radiologists found that volume did not explain much of the observed interradiologist variability in screening or diagnostic performance (4,5). The FPRs of radiologists with higher annual volumes were clinically and significantly lower than those of their lower-volume colleagues; however, the sensitivities were similar (4,5).…”
Section: Subjectsmentioning
confidence: 70%
“…The FPRs of radiologists with higher annual volumes were clinically and significantly lower than those of their lower-volume colleagues; however, the sensitivities were similar (4,5). Interpretive volume composition (ratio of screening volume relative to total volume) had the strongest influence on screening and diagnostic performance; a higher screening focus (ratio of screening to diagnostic mammograms) was associated with significantly lower screening sensitivity, cancer detection rate (CDR), and FPR (4,5), which suggests that having some element of diagnostic work-up could increase sensitivity and CDR. To our knowledge, only one study has examined whether radiologists' accuracy (defined as positive predictive value for biopsy recommendation) was influenced by monitoring a woman's images throughout the diagnostic process and found no significant influence (6).…”
Section: Subjectsmentioning
confidence: 80%
See 2 more Smart Citations
“…Because of the fact that the evaluating specialist has long experience in BI-RADS for breast radiology, we believe in the accuracy of the categorical decisions made (34). As a matter of fact, the studies performed have shown that factors influencing correct decision-making in BI-RADS include the experience of radiologist, his/her interest in dense breast radiology and the high number of studies s/he evaluates on an annual basis (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%